1997
DOI: 10.1007/s003600050101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term hypergravity on muscle, heart and lung structure of mice

Abstract: Quantitative changes in lung, heart and muscle structure were assessed in mice exposed for 14 weeks to a gravitational field of 3 G since the age of 4 weeks; matched controls were kept at normal gravity (1 G). The body mass of 3-G-exposed mice was significantly reduced by 9%, while total skeletal muscle mass remained the same fraction of body mass. The mass of the soleus muscle was found to be significantly larger in 3-G-exposed mice both in absolute (+27%) and body mass specific terms (+42%). Capillary densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…A reduction of body mass was consistently observed in weanling or mature animals as long as they remain under the acceleration field (Pitts et al 1972;Oyama et al 1985;Frey et al 1997;Smith 1973), but the animals generally recovered almost completely the control weight after 2 months at 1G (Pitts and Oyama 1979;Oyama et al 1985;Thorling and Fredens 1995;Wade et al 1997). In the present study, a slight decrease of 6.4%, in males, and 10.9%, in females, persisted in the average body mass of HG mice at the age of 9 months.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A reduction of body mass was consistently observed in weanling or mature animals as long as they remain under the acceleration field (Pitts et al 1972;Oyama et al 1985;Frey et al 1997;Smith 1973), but the animals generally recovered almost completely the control weight after 2 months at 1G (Pitts and Oyama 1979;Oyama et al 1985;Thorling and Fredens 1995;Wade et al 1997). In the present study, a slight decrease of 6.4%, in males, and 10.9%, in females, persisted in the average body mass of HG mice at the age of 9 months.…”
Section: Discussionmentioning
confidence: 88%
“…Overall, centrifuged adults showed an increased relative mass of antigravity muscles, and no change or a slight increase of non weightspecific muscles (Frey et al 1997;Stevens et al 2003;Roy et al 1996), whereas animals born and grown in HG showed a stable relative mass of postural muscles and a stable or decreasing relative mass of non postural muscles (Picquet et al 2002;Oyama et al 1985). In the present study, HG mice showed a significantly smaller force in the grip strength test, in relation with the reduction of their body mass, but they did not differ from control when the force was normalized relative to the body mass.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This increase in Sol weight is more likely associated with an increase in connective tissue 33 or complexes of the extracellular matrix 34, 35 . There are reports showing that an exposure to greater levels of gravitational field (3G) for 4 or 14 weeks can result in a significant increase in mouse Sol weight as well as CSA of Sol muscle fibres 36, 37 .…”
Section: Discussionmentioning
confidence: 99%
“…We did not have to stimulate directly or do any operations. Although such a stress as blood flow change and dullness of sense of balance were thought to be involved in centrifugation, they did not lead to a large amount of weight loss if the gravity was not so strong 7) .…”
Section: Introductionmentioning
confidence: 99%